2008
DOI: 10.1038/sj.bjc.6604320
|View full text |Cite
|
Sign up to set email alerts
|

The rexinoid, bexarotene, prevents the development of premalignant lesions in MMTV-erbB2 mice

Abstract: Retinoids, vitamin A analogues that bind to retinoic acid receptor (RAR) or retinoid X receptor (RXR), play important roles in regulating cell proliferation, apoptosis, and differentiation. Recently, RXR-selective ligands, also referred to as rexinoids, have been investigated as potential chemopreventive agents for breast cancer. Our previous studies demonstrated that the rexinoid bexarotene significantly prevented ER-negative mammary tumourigenesis with less toxicity than naturally occurring retinoids in anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 31 publications
(33 reference statements)
2
35
0
Order By: Relevance
“…Potential implementation of much lower doses of bexarotene (20, 10 mg/kg bw) may distinguish cellular senescence from apoptosis and cell proliferation, as has been reported for in vitro studies. Bexarotene was highly efficacious in inducing cellular senescence in TEBs, which have high proliferation activity and are considered places of origin of most mammary tumors, thus supporting our data and those of others that retinoids and rexinoids are more efficacious in inhibiting early than late (MIN, tumors) stages of mammary carcinogenesis (16,23).…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…Potential implementation of much lower doses of bexarotene (20, 10 mg/kg bw) may distinguish cellular senescence from apoptosis and cell proliferation, as has been reported for in vitro studies. Bexarotene was highly efficacious in inducing cellular senescence in TEBs, which have high proliferation activity and are considered places of origin of most mammary tumors, thus supporting our data and those of others that retinoids and rexinoids are more efficacious in inhibiting early than late (MIN, tumors) stages of mammary carcinogenesis (16,23).…”
Section: Discussionsupporting
confidence: 78%
“…Our data confirm previous studies of Brown's group, which found that bexarotene suppressed mammary carcinogenesis and tumor growth in MMTV-Neu mice and that this was associated with inhibition of cell proliferation (12,16). For assessment of apoptosis, we used the TUNEL assay, whereas Brown's group used the caspase-3 assay that may explain the differences in the percentage of cells in apoptosis between their and our study.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations